ANALISIS SINTAKSIS PARTIKEL DALAM AL QURAN - Ahmad Miftahuddin; Singgih Kuswardono (Lisanul Arab: Journal of Arabic Learning and Teaching, 2023)
A particle or called charf in Arabic is something that shows meaning only with another. Particles in the Arabic tradition number approximately 80 and can be grouped based on their action, inflection, meaning, and consonants. The holy book Al-Quran besides having a central role as the main source of Islamic teachings also occupies the most important position in Arabic. The Holy Quran is the basis for standard Arabic or scientific Arabic. In the Holy Quran, there are particles with various categories based on their actions, inflections, meanings, and consonants. Based on the various particle categories in the Holy Quran, in addition to the position of the Holy Quran which is very central in Arabic, it is necessary to carry out research in the field of syntax to make a general scientific contribution in the field of Arabic syntax. Based on research that has been done on particles in the Koran, there are 232 data found, consisting of 35 data based on action particles, 35 data based on inflectional particles, 102 data based on syntactic meaning, and 60 data based on particles based on their constituent consonants.